Agriculture Value Chain Financing: An Analysis of India - Bajwa, Rubeena (Indian Journal of Finance, 2013)
Agriculture continues to be the mainstay of developing economies and is the predominant source of livelihood for people in the developing world, including Asia. However, the share of agriculture in the overall GDP seems to be slipping, and for developing countries like India, this calls for action. Value chain financing for agriculture as an approach is increasingly applied by the financial institutions and by those involved in value chains. Agriculture value chain covers the activities involved in moving the products from the farmers' fields to the consumers' tables. The paper is based on the premise that the role of funding is paramount to achieve growth in the agriculture sector, thus helping in poverty alleviation in India. I have highlighted the key value chain activities in context of agricultural products and have discussed the importance of value chain financing which requires due attention from national and regional level financing corporations.